Phenomenology of Institutional Deprivation: Revitalization Aspects - Hoshovskyi, Yaroslav (Psychological Prospects Journal, 2015)
The article highlights the main approaches to understanding the content and functional essence of the phenomenon of institutional (establishment) deprivation. The negative and inhibitory role of deprivation limits on general personality development of family care deprived children is marked out. It is emphasized, that the different types of mental deprivation, which are cultivated at teaching and educational establishments of closed type, to the most extent retards personal psychogenesis progress, staining it by discomfortable and deviant segments. It is outlined, that institutional deprivation is socio-existential fact of the utmost importance, because acquires features of permanent personal crisis and disfunction and, in fact, is always challenge for normal evolution and ontogenesis of human as psychosocial being. It is noted, that by its depth and power, institutional deprivation threatens the entire development at all levels, leading to specific involution - social outsider. It is stated, that as result of deprivation syndrome experience in children boarding school, decrease in general vital stability and level of psychosocial balance of pupil is happening, and the process of its formation is characterized by narrowing of communicative activity, psychoemotional fragmentation and tendencies to social autism, asthenia, depression, etc. Family care deprived children, staying in deprivation mode, undergo multiple social and psychological problems and destructions, and their everyday life activity is obscured by different types of development limits, affecting the basic constructs of psychostructure and negatively influence on biodrome self experience of every child. Lack of family interaction, insufficient sensory stimulation, limitation and monotony of living conditions of child in boarding type institutions are very important, but they are not fatal, because active and targeted professional revitalization (psychorehabilitation, psychocorrection, recreation and other effects), “compensatory successes” or also significant and positive personality prosocial changes are possible.